CLASSROOM-BASED EDUCATIONAL HEARING CONSERVATION PROGRAMME: ADDRESSING THE CONTENTS AND CHALLENGES - ISHAK, KAMARUL AKMAL; ISMAIL, NORAIDAH; RAHMAT, SARAH (International Journal of Allied Health Sciences, 2021)
Introduction: Nowadays, leisure noise exposure has become a public health concern. Young adults or youth are often exposed to a high level of noise, particularly from leisure and recreational activities. Although the implementation of classroom-based educational hearing conservation programme (EdHCP) is proven in improving youth’s attitude, knowledge, and behaviour on the danger of leisure noise exposure, a formal programme targeted for young adults is yet to be developed in Malaysia. Objective: This paper aims to review the contents of the existing classroom-based EdHCP and identify the challenges faced in ensuring the sustainability of the programme. Methodology: Four classroom EdHCPs were identified and analysed. The objective, targeted participants, learning modules, materials, and timeframe were reviewed. The efficiency of the programmes was discussed individually, and the obstacles and experts’ recommendations for the programmes sustainability were acknowledged. Result: Generally, the reviewed programmes have a similar goal, which is to minimise the incident of noise-induced hearing loss (NIHL). Although they are specified for the schoolchildren, the contents and activities can be modified when focusing on young adults. Conclusion: Sufficient materials and resources are available to convey the messages of healthy hearing behaviour among the students. The information obtained is crucial as they will guide and provide references to develop a Malay classroom EdHCP targeting the young adults in Malaysia. Nevertheless, the sustainability of the future developed programme should be prioritised and taken into consideration.